Policy reform toward gender equality in Ethiopia: Little by little the egg begins to walk - Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2012)
There is growing interest in the role of policy reforms to promote gender equality and empower women, two key objectives of development policy. From a policy perspective, it would be ideal for reforms undertaken in different policy areas to be consistent, so that they reinforce each other in improving gender equity. We use data from the Ethiopian Rural Household Survey (ERHS) to show how two seemingly unrelated reforms—community-based land registration, undertaken since 2003, and changes in the Family Code implemented in 2000—may have created conditions for mutually reinforcing gender-sensitive reforms. Our analysis confirms previous studies’ findings of gender gaps in awareness and information about the land registration process. Male-headed households are, on average, more likely to have heard about the process, to have attended meetings (and a greater number of meetings), and to have received some written material with information about the process. Having female members in the Land Administration Committee (LAC) has a positive impact on attendance at meetings relating to land registration. In our analysis of the changes in the family law, we find that awareness about the land registration process is positively correlated with the shift in perceptions toward equal division of land and livestock upon divorce. The presence of female members in the LAC also has a positive effect on the shift in perceptions toward a more equal division of assets upon divorce. Taken together, these findings suggest that the land registration process and the reform of the Family Code may have mutually reinforcing effects on women’s rights and welfare. While this example is obviously rooted in the Ethiopian context, it raises the possibility that similar reform efforts may be complementary in other countries as well.